2015
DOI: 10.4062/biomolther.2015.013
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metabolism: Strategic Diversion from Targeting Cancer Drivers to Targeting Cancer Suppliers

Abstract: Drug development groups are close to discovering another pot of gold-a therapeutic target-similar to the success of imatinib (Gleevec) in the field of cancer biology. Modern molecular biology has improved cancer therapy through the identification of more pharmaceutically viable targets, and yet major problems and risks associated with late-phase cancer therapy remain. Presently, a growing number of reports have initiated a discussion about the benefits of metabolic regulation in cancers. The Warburg effect, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Although the concept of cancer metabolism was introduced over 70 years ago by Dr. Warburg [18], the source of energy and the supply mechanism in cancer tumors has not been clearly understood for two reasons. First, glucose dependency may change under various culture conditions, and second, there are multiple energy metabolism pathways depending on different nutrition sources.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of cancer metabolism was introduced over 70 years ago by Dr. Warburg [18], the source of energy and the supply mechanism in cancer tumors has not been clearly understood for two reasons. First, glucose dependency may change under various culture conditions, and second, there are multiple energy metabolism pathways depending on different nutrition sources.…”
Section: Discussionmentioning
confidence: 99%
“…7 This concept is based on the idea that inhibition of cellular bioenergetics could possibly override oncogenic signaling pathways. Because cancer cells are more dependent on glycolysis (Warburg effect), 25 there have been various attempts to block glycolysis as a strategy for inhibiting cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 Modulation of cancer cell metabolism, one of the emerging therapeutic targets proposed to overcome this limitation, is considered a promising therapeutic approach. 7 2-Deoxyglucose (2DG), which is closely related to cellular energy restriction, has been shown to inhibit cancer cell proliferation in pancreatic cancer 8 and breast cancer cell models. 9 Moreover, it has been reported that 2DG becomes a more effective anticancer agent when combined with biguanide, which inhibits mitochondrial oxidative phosphorylation.…”
mentioning
confidence: 99%
“…After reviewing the existing literature, we come to a tentative conclusion that cancer metabolism may be regarded as a beacon of hope for cancer research (Kim, 2015;Phan, Yeung, and Lee, 2014), eventually opening the gate of tremendous growth opportunities for nations. As a consequence, many biopharmaceutical and biotechnology companies have invested in cancer metabolism-related research or technologies.…”
Section: Network Analysis On Cancer Metabolismmentioning
confidence: 99%
“…However, there is little attention paid to monitoring the activities from a strategic perspective. Even though some studies (Khanna, 2012;Vermeersch, and Styczynski, 2013;Phan, Yeung, and Lee, 2014;Kim, 2015;Cheong, 2013) focused on such issues, they mostly suggested a strategic research and development (R&D) direction for diagnosis and therapies through reviewing recent remarkable advances in this field. To be competitive, it is necessary for managers to understand the overall status quo of the cancer metabolism-related scientific arena.…”
Section: Network Analysis On Cancer Metabolismmentioning
confidence: 99%